The analysis of modern ways of sampling personnel - Rimkevičiūte, Giedrė (Technological and Economic Development of Economy, 2004)
This article includes the analysis of modern ways of sampling personnel. Several ways are presented in detail: the significance of the section of personnel, the methods of searching personnel in Lithuania and in the world's practice, job agencies in Lithuania ‐ their types and advantages, the specifics of job hunting in different sources. The conclusions about searching for personnel on‐line: advantages, shortcommings, technical aspects (are given different ways of searching for personnel), effectiveness (in percents) are compared. Some aspects are illustrated by pictures (the most effective ways of searching for personnel).Article in Lithuanian.Šiuolaikinių personalo atrankos būdų analizėFirst Published Online: 21 Oct 2010